Blue Economy and Sustainable Development: A Comparative Analysis of International Models and Türkiye’s Governance Capacity - Abdallah Abukalloub; Ayşe Güngör (Apollo: Journal of Tourism and Business, 2026)
The blue economy is a holistic development approach that seeks to balance economic growth, environmental protection, and social welfare through the sustainable use of marine and ocean resources. This study examines the relationship between the blue economy approach and the Sustainable Development Goals and evaluates Türkiye’s potential in this field through comparative country cases. The research adopts a qualitative design based on document analysis and comparative case study methods. In this context, reports of international organizations, policy documents, and academic studies were analyzed, and the experiences of Portugal, Indonesia, and the Maldives were compared in terms of blue economy strategies, institutional structures, priority sectors, and governance capacities. The findings suggest that the blue economy should not be considered merely as a growth model aimed at expanding marine-based economic activities. Rather, it represents a comprehensive development paradigm that requires ecosystem-based planning, multi-level governance, sustainable resource management, and long-term policy coordination. The comparative analysis further indicates that successful blue economy practices are supported by strong institutional capacity, cross-sectoral integration, and environmental sustainability principles. For Türkiye, sectors such as maritime transport, ports, aquaculture, coastal tourism, renewable marine energy, and marine biotechnology present significant opportunities. However, institutional fragmentation, data limitations, pressures on coastal ecosystems, and the absence of a comprehensive national strategy remain key challenges. By addressing the blue economy within an integrated governance and sustainability framework, this study contributes to the literature on sustainable maritime development.